Mesenteric Meckel's diverticulum: an unusual cause of small bowel intussusception - Abbas, S; Akbari, K; Mason, J; Booth, M (BMJ Publishing Group, 2016)
Meckel's diverticulum (MD) is the commonest congenital anomaly of the small intestine, affecting 1–4% of the population. Cardinal features emphasise an antimesenteric location two feet proximal to the ileocaecal valve, with a separate mesenteric blood supply and involvement of all layers of the small intestine. However, reports of MD arising from the mesenteric border of the small intestine are rare in the surgical literature. This report examines the case of a 45-year-old woman presenting with a 6-month history of episodic central abdominal pain and microcytic anaemia who underwent an elective diagnostic laparoscopy as initial CT findings were inconclusive. Intraoperatively, she was found to have small bowel intussusception approximately 40 cm proximal to the ileocaecal valve. Macroscopic examination of the resected small bowel segment revealed a mesenteric outpouching that was confirmed as mesenteric MD on histopathological analysis. Postoperatively, the patient recovered with no surgical complications and full symptom resolution.